Soil survey of an area in Atchison county Kansas - McLenon, H. A. (My University, 1908)
Introduction: The area of this survey consists of a strip of territory three miles wide and twenty-six miles long, and comprises about 49,280 acres or 77 square miles. The survey runs through the central part of Atchison county.
Citation: McLenon, H. A. Soil survey of an area in Atchison county Kansas. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Kansas; Soil; Agriculture; Graduating theses; Senior theses; Theses